Infaq Sterilization Box with UV and Ozone (BIUZ) - Arifin, Zaenal; Tamamy, Aries Jehan; Pamungkas, Hery; Mayasari, Dita Ayu; Heryanto, M Ary (JURNAL NASIONAL TEKNIK ELEKTRO, 2022)
The COVID-19 pandemic that has occurred to date has resulted in the loss of many lives. This is due to the ease with which the COVID-19 virus spreads. According to the latest research published by the WHO, the virus can spread through the medium of objects, one of the easies object to spread virus is money. The spread of the COVID-19 virus can be done through money transactions that have previously been used by people infected by the virus. This is because COVID-19 virus can survive for more than 72 hours. To prevent this, it is necessary to sterilize so that the virus in the money can be neutralized. The technology that can be used for disinfection in this tool is Ultra Violet (UV) light and Ozone Generator. Many studies have shown that UV rays and ozone gas (O3) are able to kill viruses that are on the surface of objects. The ability of UV rays and ozone gas (O3) can kill viruses in money because UV rays and ozone gas (O3) have radiation that is quite harsh, so that if exposed to human skin continuously it can cause damage to skin tissue. In this study, to overcome this problem, a device that is automatically able to carry out the disinfection process in the room is made by utilizing UV light. Infaq Sterilization Box with UV and Ozone (BIUZ) can kill viruses in money, it is also easy to operate and safe. The size of the tool made is adjusted to the object or partner of the research activity, namely the Central Java Great Mosque Manager (PP MAJT). The need for partners is that the tool is able to carry out the sterilization process of infaq money provided by the congregation, both in the form of paper and coins effectively.